Perbandingan Cbr dan Ucs Tanah Lempung Distabilisasi Pasir dan Semen - Anwar Muda (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
California Bearing Ratio (CBR) is the ratio between load penetration of a substance against a standard material with the depth and penetration of the same speed. While Unconfined Compression Strength (UCS) is the amount of axial load per unit area at the time of the test specimen to collapse or when the axial strain reaches 20%. This study aimed to compare the CBR and UCS clay stabilized sand and cement for the pavement. The results showed that the CBR value increases, the value rises with increasing UCS cement mix. Then when the stabilization of clay with a mixture of 12% sand and 10% cement values obtained UCS at 9.06 kg/cm2 and CBR of 66% thus, stabilization of clay Bukit Rawi qualify for base down the highway because of the value of UCS 9.06 kg/cm2 > UCS 6 kg/cm2 and CBR of 66% > 20%. UCS and CBR rise in value is due to that the addition of semen into adhesive media when it reacts with water. Media adhesive is then solidified and formed a hard mass so it would hold weight.